2016
DOI: 10.1098/rsbl.2016.0653
|View full text |Cite
|
Sign up to set email alerts
|

Repeated evolution of viviparity in phrynosomatid lizards constrained interspecific diversification in some life-history traits

Abstract: In vertebrates, viviparity has evolved independently multiple times, apparently increasing morphological diversification and speciation rates as a consequence. We tested whether the evolution of viviparity has also increased diversification of life-history traits by estimating evolutionary rates of lizards from the North American family Phrynosomatidae. Using modern phylogenetic comparative methods, we compared these rates between oviparous and viviparous species, and found no support for this hypothesis. Inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…Further, El Capulín S. palaciosi does not show a male/female asynchronous reproductive cycle, in contrast to the Monte Alegre population (Méndez & Villagrán, 1998). These differences and similarities in reproductive cycles between species and among conspecific populations could be a result of three components: physiological, environmental and phylogenetic (Dunham & Miles, 1985;Ramírez-Bautista et al, 2017;Zúñiga-Vega et al, 2016). Another difference in reproductive activity between El Capulín and Monte Alegre females (Méndez & Villagrán, 1998) is that in the latter population, female reproductive activity was negatively correlated with temperature and photoperiod.…”
Section: Female Reproductive Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…Further, El Capulín S. palaciosi does not show a male/female asynchronous reproductive cycle, in contrast to the Monte Alegre population (Méndez & Villagrán, 1998). These differences and similarities in reproductive cycles between species and among conspecific populations could be a result of three components: physiological, environmental and phylogenetic (Dunham & Miles, 1985;Ramírez-Bautista et al, 2017;Zúñiga-Vega et al, 2016). Another difference in reproductive activity between El Capulín and Monte Alegre females (Méndez & Villagrán, 1998) is that in the latter population, female reproductive activity was negatively correlated with temperature and photoperiod.…”
Section: Female Reproductive Cyclementioning
confidence: 99%
“…These similarities or differences are expressed in morphological attributes of life history traits (Stearns, 93; Wang, Zhao, Ji, Yu, & Liu, 96; Zúñiga‐Vega, Fuentes‐G, Ossip‐Drahos, & Martins, 99). The similarities are more easily detected within species groups within highly diverse genera, such as the genus Sceloporus (Leaché, Banbury, Linkem, & Nieto‐Montes de Oca, 36; Zúñiga‐Vega et al, 99). For example, recent studies have shown that two species of the Spinosus group, Sceloporus spinosus and Sceloporus horridus show similar clutch sizes and offspring SVLs at birth (Ramírez‐Bautista et al, 73; Valdéz‐González & Ramírez‐Bautista, 94; Valencia‐Limón, Castro‐Franco, & Bustos‐Zagal, 95).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the viviparity among reptiles has been linked to cold 36 climates, because it provides a selective advantage that prevents the death of embryos in the 37 nest caused by low temperatures (Tinkle & Gibbons, 1977;Shine, 1985; Lambert & Wiens, 38 2013), and could be considered a phylogenetic constraint (Tinkle & Gibbons, 1977;Uller, 2003). 39 For example, there is evidence that viviparity among phrynosomatid lizards constrained some 40 life-history traits (Zúñiga-Vega et al, 2016). Thus, we expected that viviparous species share 41 environmental affinities that could lead to a stabilized selection and, as a consequence, show 42 PNC, at least in some characteristics linked with breeding season, and for instance with cold 43 environments.…”
mentioning
confidence: 99%
“…For example, there is evidence that viviparity among phrynosomatid lizards constrained some life-history traits (Zúñiga-Vega et al, 2016). Thus, we expected that viviparous species share environmental affinities that could lead to a stabilized selection and, as a consequence, show PNC, at least in some characteristics linked with breeding season, and for instance with cold environments.…”
Section: Introductionmentioning
confidence: 97%